Ophelia [videorecording (DVD)] - McCarthy, Claire (Director); Ridley, Daisy, 1992-; Watts, Naomi, 1968-; Owen, Clive; Shakespeare, William, 1564-1616 (Shout! Factory, 2019)
In a story based on Shakespeare's Hamlet, Ophelia tells of her life in the court at Elsinore, her love for Prince Hamlet, and her escape from the violence in Denmark.